Temperature dependence of the reactivity of cemented paste backfill. (September 2016) - Aldhafeeri, Z.; Fall, M.; Pokharel, M.; Pouramini, Z.
Abstract: The environmental performance of cemented paste backfill (CPB; a mixture of tailings, water and binder), which contains sulphide mineral-bearing tailings, is strongly influenced by its reactivity. However, our understanding of the reactivity of CPB under various thermal loading conditions as well as its evolution with time is limited. Hence, a laboratory investigation is conducted to study the effects of curing and ambient (atmospheric) temperatures on the reactivity of CPB. Oxygen consumption (OC) tests are conducted on CPB specimens cured at different temperatures to study their reactivity. Furthermore, microstructural analyses (e.g., x-ray diffraction (XRD), mercury intrusion porosimetry, and thermogravimetry/derivative thermogravimetry) are performed to assess the microstructural characteristics of the tested CPBs. The results show that the reactivity of CPB is temperature-dependent. As the curing temperature increases, the reactivity generally decreases. The reactivity is also affected by the ambient temperature. The reactivity increases as the atmospheric temperature increases. However, the extent of the effect of the temperature depends on the curing time and is generally more pronounced at the early ages. Furthermore, the presence of sulphate in the pore water of CPB can significantly affect the reactivity of CPB cured at high temperatures (50 °C). The findings of this study will therefore help to better assess and predict the environmental behavior of CPB under various field thermal conditions. Highlights: Oxygen consumption is most preferred technique to measure the reactivity of cemented paste backfill (CPB). The reactivity of CPB is temperature-dependent. The reactivity decreases with increasing the curing temperature. The reactivity increases as the atmospheric temperature increases. The presence of sulphate ions in the pores of CPB can significantly affect the reactivity.